A really wheezy way to save money. Issue 3 (26th February 2016) - Taylor, Felicity J; Li, Grace; Almossawi, Ofran; Dulfeker, Hasna; Jones, Victoria
Abstract : Evaluating the cost-saving potential of switching prednisolone formulation in the treatment of childhood wheeze.